Gambaran Pengetahuan Pasien Pra Operasi Tentang Pentingnya Puasa Sebelum Tindakan Operasi di RSUD Pidie Jaya - Noval Aulia; Tophan Heri Wibowo; Feti Kumala Dewi (LPPM Universitas Harapan Bangsa, 2023)
Pre-surgical information for patients is important for patients to know so that they are better prepared for the surgical process. Inadequate pre-surgical preparation can be a cause of anesthetic accidents. This study aims to describe the knowledge of preoperative patients about the importance of fasting before surgery at Pidie Jaya Hospital. This research method is quantitative with a descriptive approach. Sampling technique with nonprobability sampling by means of accidental sampling as many as 104 respondents who perform operations. Data analysis was performed univariately. The results showed that the majority of patients aged > 35 years were 59 respondents (56.7%), the majority were male, 63 respondents (60.6%), the majority had junior high school education, 61 respondents (58.7%), the majority 37 respondents (35.6%) worked as farmers, the majority had never undergone surgery, namely 92 respondents (88.5%). The majority of preoperative patients' knowledge about the importance of fasting is in the less category, namely as many as 43 respondents (41.3%). This study concluded that the knowledge of preoperative patients about the importance of fasting at Pidie Jaya General Hospital was mostly in the less category